2017
DOI: 10.1177/0886260517715025
|View full text |Cite
|
Sign up to set email alerts
|

Attributing Responsibility, Sexist Attitudes, Perceived Social Support, and Self-Esteem in Aggressors Convicted for Gender-Based Violence

Abstract: This work analyzes how the assumption of responsibility by aggressors convicted for gender-based violence is related to sexist attitudes, self-esteem and perceived functional social support. Similarly, the predictive capacity of these variables is studied with respect to the aggressors' minimization of the harm done and a lack of attributing responsibility to themselves. The participants in the research were males condemned to prison sentences for crimes related with gender-based violence in Spain. The instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
4
0
5
Order By: Relevance
“…Social and moral norms based on inequality appear to play an important role in batterer behavior and could provide the basis for the motivation to commit violent acts (Devries et al., 2013). In addition, it has been found that sexist attitudes in batterers are related to a greater lack of attribution of responsibility and a greater tendency to minimize the harm caused (Guerrero-Molina et al., 2017). With respect to the lack of responsibility for aggressive behavior, they use processes of moral disassociation to justify such behavior (Bussey et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Social and moral norms based on inequality appear to play an important role in batterer behavior and could provide the basis for the motivation to commit violent acts (Devries et al., 2013). In addition, it has been found that sexist attitudes in batterers are related to a greater lack of attribution of responsibility and a greater tendency to minimize the harm caused (Guerrero-Molina et al., 2017). With respect to the lack of responsibility for aggressive behavior, they use processes of moral disassociation to justify such behavior (Bussey et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, a través del análisis de regresión logística binaria se encontró que el componente hostil es, precisamente, el que se vincula con circunscribir la violencia a un asunto del ámbito privado. Esto podría estar relacionado con la justificación de la violencia ejercida y la minimización del daño cuando la atribución de responsabilidad se dirige hacia las mujeres víctimas (Rollero & De Piccoli, 2020), tal como se ha encontrado en muestras similares a las de la presente investigación (Guerrero-Molina et al, 2020a;Guerrero-Molina et al, 2020b).…”
Section: Discussionunclassified
“…Tampoco parece haber diferencias en función de la exposición a la violencia contra su madre entre quienes Tabla 5. Relación entre el grado de acuerdo respecto a que la violencia es un asunto privado y las dimensiones del asi (Bonilla-Algovia, 2021) y en trabajos con colectivos de hombres que han ejercido vcmp (Echeburúa et al, 2016;Guerrero-Molina et al, 2020a).…”
Section: Diferencias En La Consideración "La Violencia De Pareja Es U...unclassified
See 1 more Smart Citation
“…For this study, Cronbach's α was .77. This scale has been used with Spanish samples of IPVAW offenders (Catalá-Miñana et al, 2013;Guerrero-Molina et al, 2020;Lila, Gracia & Murgui, 2013).…”
Section: Personality Disorders and Psychological Adjustment Variablesmentioning
confidence: 99%